Adolescent binge drinking increases expression of the danger signal receptor agonist HMGB1 and toll-like receptors in the adult prefrontal cortex - Vetreno, R.P.; Crews, F.T. (Neuroscience, 2012)
► Adolescent binge drinking upregulates danger signal receptors in adult brain. ► Binge ethanol exposure during adolescence increases HMGB1 in adult brain. ► Adolescent binge ethanol exposure leads to long-term reversal learning deficits. ► Alcohol-induced activation of danger signaling contributes to behavioral deficits. Adolescence is a critical developmental stage of life during which the prefrontal cortex (PFC) matures, and binge drinking and alcohol abuse are common. Recent studies have found that ethanol increases neuroinflammation via upregulated high-mobility group box 1 (HMGB1) signaling through Toll-like receptors (TLRs). HMGB1/TLR ‘danger signaling’ induces multiple brain innate immune genes that could alter brain function. To determine whether adolescent binge drinking persistently increases innate immune gene expression in the PFC, rats (P25–P55) were exposed to adolescent intermittent ethanol (AIE [5.0g/kg, 2-day on/2-day off schedule]). On P56, HMGB1/TLR danger signaling was assessed using immunohistochemistry (i.e., +immunoreactivity [+IR]). In a separate group of subjects, spatial and reversal learning on the Barnes maze was assessed in early adulthood (P64–P75), and HMGB1/TLR danger signaling was measured using immunohistochemistry for +IR and RT-PCR for mRNA in adulthood (P80). Immunohistochemical assessment at P56 and 24days later at P80 revealed increased frontal cortical HMGB1, TLR4, and TLR3 in the AIE-treated rats. Adolescent intermittent ethanol treatment did not alter adult spatial learning on the Barnes maze, but did cause reversal learning deficits and increased perseverative behavior. Barnes maze deficits correlated with the expression of danger signal receptors in the PFC. Taken together, these findings provide evidence that adolescent binge drinking leads to persistent upregulation of innate immune danger signaling in the adult PFC that correlates with adult neurocognitive dysfunction.